Supplementary information: Anthropogenic organic contaminants analysed in human blood and combined risk - Engelhardt, Josefin; Weiss, Jana; Norström, Karin (Stockholm University, 2022)
The number of chemicals in the anthroposphere is increasing and some of them end up in humans. A literature search was made to assess which anthropogenic organic contaminants (OCs) that have been analysed in blood from the general population. The reviewed articles were used to create a database of studies (Human Blood Database [HBDB], containing 559 OCs) reporting blood analyses made worldwide. All studies analysing blood from the Swedish population were compiled into a second database (Swedish Exposure Database [SEDB], containing 166 OCs) listing blood concentrations of OCs. Data from the SEDB showed decreasing levels of regulated chemicals in blood over time, indicating that regulation had made an impact. The Hazard Index (HI) approach was used as a qualitative mixture risk assessment of the OCs with established human biomonitoring guidance values (HBM-GVs) and blood levels in the SEDB. Nine HBM-GVs were found and the HI of the corresponding OCs/groups of OCs showed that a risk of adverse effects in the general population could not be excluded, which is a cause for concern considering that only 6% of the analysed OCs in the SEDB were included. This study presents the OCs identified in human blood and concentration time trends. The study highlights the lack of HBM-GVs needed for mixture risk assessments to assess the combined risk of chemical exposure to the general population.

Online Resource 1 is a spreadsheet containing the two compiled databases HBDB and SEDB. Online Resource 2 provides additional concentration trends and tables not present in the article itself.
Keywords: Pollution and contamination not elsewhere classified; Health Sciences; Hälsovetenskap